2011
DOI: 10.1152/ajpgi.00141.2010
|View full text |Cite
|
Sign up to set email alerts
|

Snail1 transcription factor is a critical mediator of hepatic stellate cell activation following hepatic injury

Abstract: Following liver injury, the wound-healing process is characterized by hepatic stellate cell (HSC) activation from the quiescent fat-storing phenotype to a highly proliferative myofibroblast-like phenotype. Snail1 is a transcription factor best known for its ability to trigger epithelial-mesenchymal transition, to influence mesoderm formation during embryonic development, and to favor cell survival. In this study, we evaluated the expression of Snail1 in experimental and human liver fibrosis and analyzed its ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Thus, these findings favour the use of in vivo‐ activated HSC isolated from a fibrotic liver over in vitro‐ activated HSC , with in vivo‐ activated HSC reflecting more the specific microenvironment of HSC in the fibrotic liver. This model has been adapted by other investigators wishing to explore, in a more detailed manner, the interplay of HSC and their original microenvironment . Indeed, this concept has gained more attention and has been used to compare the behaviour of in vitro‐ activated with in vivo‐ activated HSC in different animal models/chronic diseases.…”
Section: Cross‐talk Between Tumour Cells and The Principal Producing mentioning
confidence: 99%
“…Thus, these findings favour the use of in vivo‐ activated HSC isolated from a fibrotic liver over in vitro‐ activated HSC , with in vivo‐ activated HSC reflecting more the specific microenvironment of HSC in the fibrotic liver. This model has been adapted by other investigators wishing to explore, in a more detailed manner, the interplay of HSC and their original microenvironment . Indeed, this concept has gained more attention and has been used to compare the behaviour of in vitro‐ activated with in vivo‐ activated HSC in different animal models/chronic diseases.…”
Section: Cross‐talk Between Tumour Cells and The Principal Producing mentioning
confidence: 99%
“…TGF-␤1-induced upregulation of the profibrotic genes PAI-1, TGF-␤1, collagen type I, and ␣-SMA was more pronounced in CD44s overexpressing TEC and weaker/absent in CD44v3-TEC. Accordingly, CD44v3-TEC did not show an enhanced gene expression of the transcription factor Snail-1, which is known to trigger EMT (50). As changes in mRNAs may not always translate in similar protein expression levels, we determined PAI-1 protein levels by Western blot.…”
Section: Resultsmentioning
confidence: 96%
“…This model has now been adapted by several investigators to explore in greater detail the interplay between HSCs and the changing microenvironment in the diseased liver. Indeed, this concept has gained more attention and has been used to compare the characteristics of in vitro-activated HSCs with in vivo-activated HSCs in different animal models/chronic diseases [32][33][34]. Furthermore, fate tracking in combination with new markers in in vivo models has confirmed that activated HSCs are the major source of myofibroblasts and liver fibrosis [35,36].…”
Section: In Vitro-versus In Vivo-activated Hscsmentioning
confidence: 99%